2014 IEEE 27th International Conference on Micro Electro Mechanical Systems (MEMS) 2014
DOI: 10.1109/memsys.2014.6765643
|View full text |Cite
|
Sign up to set email alerts
|

LoC sensor array platform for real-time coagulation measurements

Abstract: 1This paper reports a MEMS-based sensor array enabling multiple clot-time tests in one disposable microfluidic cartridge using plasma. The versatile LoC (Lab-on-Chip) platform technology is demonstrated here for real-time coagulation tests (activated Partial Thrompoblastin Time (aPTT) and Prothrombin Time (PT)). The system has a reader unit and a disposable cartridge. The reader has no electrical connections to the cartridge, which consists of multiple microfluidic channels and MEMS microcantilevers placed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Sensor and cartridge fabrication was performed using a procedure as reported in our earlier studies. 21,23,24 Briefly the nickel cantilevers were fabricated by a simple one mask process utilizing sputter, photolithography, electrodeposition and wet etching steps. The fabricated nickel cantilevers were 200 μm long, 20 μm wide and 2 μm thick.…”
Section: Sensor and Cartridge Fabricationmentioning
confidence: 99%
“…Sensor and cartridge fabrication was performed using a procedure as reported in our earlier studies. 21,23,24 Briefly the nickel cantilevers were fabricated by a simple one mask process utilizing sputter, photolithography, electrodeposition and wet etching steps. The fabricated nickel cantilevers were 200 μm long, 20 μm wide and 2 μm thick.…”
Section: Sensor and Cartridge Fabricationmentioning
confidence: 99%
“…The cantilever utilized in this study is fabricated utilizing an easy, single mask process utilising many stages [24][25][26]. Using Ansys code of the research presents the design, simulation as shown in Figure 4(a&b) shows the coil between two magnets in 3D.…”
Section: Results and Simulationsmentioning
confidence: 99%